DETERMINANTS OF PSYCHOLOGICAL CONFLICT IN JO PIAZZA’S EVERYONE IS LYING TO YOU - Muhammad Naufal Ammar Mu'ammar; Thohiriyah (English Literature Department, Faculty of Economics, Law, and Humanities, 2026)
Psychological conflict is a central concern in contemporary literary studies because it reveals how individuals negotiate identity, desire, and control within increasingly complex social environments. However, existing literary analyses often privilege intrapsychic tension while giving limited attention to how external forces, particularly domestic oppression and digital influencer culture, actively shape and intensify psychological struggle. Addressing this gap, this study examines the internal and external psychological determinants that shape Rebecca Sommers's psychological conflict in Jo Piazza’s Everyone Is Lying to You. This research employs a qualitative descriptive method, using the novel as primary data in the form of narration, dialogue, and character actions. The data are analyzed through Freudian psychoanalytic theory, focusing on the interaction of the Id, Ego, and Superego, while situating these psychic structures within the socio-cultural context of patriarchal domestic control and influencer-driven digital culture. The findings indicate that Rebecca’s psychological conflict arises from an ongoing struggle between instinctual desires for autonomy, ego-driven strategies of self-regulation, and superego-based moral pressure, all of which are significantly intensified by domestic oppression, social media pressure, and social isolation. These external determinants operate as active psychological forces that enforce self-surveillance, regulate behavior, and perpetuate repression rather than functioning merely as background conditions. This study concludes that psychological conflict in contemporary literary narratives cannot be fully understood without integrating intrapsychic dynamics with external socio-digital determinants, demonstrating how influencer culture and domestic power structures reshape individual psychology.